Effect of dewatering aid dosage in electroforced sedimentation - Alam, Md. Monjurul; Jami, Mohammed Saedi; Alam, Md. Zahangir; Iwata, Masashi (2014)
Nowadays wastewater treatment plants are producing huge amount of sludge. The water content of the traditionally dewatered sludge, resulting from drying beds, centrifuges, vacuum filters, screw press filters and pressure filters, remains a critical factor affecting the choice of transportation vehicles, transportation costs, and suitability of sludge for incineration. The objective of this study is to investigate the role of polyacrylamide dose and constant current density on the electroforced sedimentation of sludge dewatering process. Zinc Oxide slurry was used as model sludge. Electroforced sedimentation experiments of zinc oxide suspended in aqueous media with and without polyacrylamide were carried out under various constant electric current densities. It was observed that at the same constant electric current density, the voltage difference was decreasing with the increase of polyacrylamide dose. Moreover, the highest sedimentation rate was attributed at 1.5% polyacrylamide in electroforced sedimentation of zinc oxide slurry under different constant current densities.